If the integral as written in my comment is accurate, then we have
![I=\displaystyle\int_{3/2}^2\sqrt{(x-1)(3-x)}\,\mathrm dx](https://tex.z-dn.net/?f=I%3D%5Cdisplaystyle%5Cint_%7B3%2F2%7D%5E2%5Csqrt%7B%28x-1%29%283-x%29%7D%5C%2C%5Cmathrm%20dx)
Expand the polynomial, then complete the square within the square root:
![(x-1)(3-x)=-x^2+4x-3=1-(x-2)^2](https://tex.z-dn.net/?f=%28x-1%29%283-x%29%3D-x%5E2%2B4x-3%3D1-%28x-2%29%5E2)
![I=\displaystyle\int_{3/2}^2\sqrt{1-(x-2)^2}\,\mathrm dx](https://tex.z-dn.net/?f=I%3D%5Cdisplaystyle%5Cint_%7B3%2F2%7D%5E2%5Csqrt%7B1-%28x-2%29%5E2%7D%5C%2C%5Cmathrm%20dx)
Let
and
:
![I=\displaystyle\int_{\pi/3}^{\pi/2}\sqrt{1-(2-\cos\theta-2)^2}\sin\theta\,\mathrm d\theta](https://tex.z-dn.net/?f=I%3D%5Cdisplaystyle%5Cint_%7B%5Cpi%2F3%7D%5E%7B%5Cpi%2F2%7D%5Csqrt%7B1-%282-%5Ccos%5Ctheta-2%29%5E2%7D%5Csin%5Ctheta%5C%2C%5Cmathrm%20d%5Ctheta)
![I=\displaystyle\int_{\pi/3}^{\pi/2}\sqrt{1-\cos^2\theta}\sin\theta\,\mathrm d\theta](https://tex.z-dn.net/?f=I%3D%5Cdisplaystyle%5Cint_%7B%5Cpi%2F3%7D%5E%7B%5Cpi%2F2%7D%5Csqrt%7B1-%5Ccos%5E2%5Ctheta%7D%5Csin%5Ctheta%5C%2C%5Cmathrm%20d%5Ctheta)
![I=\displaystyle\int_{\pi/3}^{\pi/2}\sqrt{\sin^2\theta}\sin\theta\,\mathrm d\theta](https://tex.z-dn.net/?f=I%3D%5Cdisplaystyle%5Cint_%7B%5Cpi%2F3%7D%5E%7B%5Cpi%2F2%7D%5Csqrt%7B%5Csin%5E2%5Ctheta%7D%5Csin%5Ctheta%5C%2C%5Cmathrm%20d%5Ctheta)
Recall that
for all
, but for all
in the integration interval we have
. So
:
![I=\displaystyle\int_{\pi/3}^{\pi/2}\sin^2\theta\,\mathrm d\theta](https://tex.z-dn.net/?f=I%3D%5Cdisplaystyle%5Cint_%7B%5Cpi%2F3%7D%5E%7B%5Cpi%2F2%7D%5Csin%5E2%5Ctheta%5C%2C%5Cmathrm%20d%5Ctheta)
Recall the double angle identity,
![\sin^2\theta=\dfrac{1-\cos(2\theta)}2](https://tex.z-dn.net/?f=%5Csin%5E2%5Ctheta%3D%5Cdfrac%7B1-%5Ccos%282%5Ctheta%29%7D2)
![I=\displaystyle\frac12\int_{\pi/3}^{\pi/2}(1-\cos(2\theta))\,\mathrm d\theta](https://tex.z-dn.net/?f=I%3D%5Cdisplaystyle%5Cfrac12%5Cint_%7B%5Cpi%2F3%7D%5E%7B%5Cpi%2F2%7D%281-%5Ccos%282%5Ctheta%29%29%5C%2C%5Cmathrm%20d%5Ctheta)
![I=\dfrac\theta2-\dfrac{\sin(2\theta)}4\bigg|_{\pi/3}^{\pi/2}](https://tex.z-dn.net/?f=I%3D%5Cdfrac%5Ctheta2-%5Cdfrac%7B%5Csin%282%5Ctheta%29%7D4%5Cbigg%7C_%7B%5Cpi%2F3%7D%5E%7B%5Cpi%2F2%7D)
![I=\dfrac\pi4-\left(\dfrac\pi6-\dfrac{\sqrt3}8\right)=\boxed{\dfrac\pi{12}+\dfrac{\sqrt3}8}](https://tex.z-dn.net/?f=I%3D%5Cdfrac%5Cpi4-%5Cleft%28%5Cdfrac%5Cpi6-%5Cdfrac%7B%5Csqrt3%7D8%5Cright%29%3D%5Cboxed%7B%5Cdfrac%5Cpi%7B12%7D%2B%5Cdfrac%7B%5Csqrt3%7D8%7D)
You can determine the more general result in the same way.
![I=\displaystyle\int_p^q\sqrt{(x-a)(b-x)}\,\mathrm dx](https://tex.z-dn.net/?f=I%3D%5Cdisplaystyle%5Cint_p%5Eq%5Csqrt%7B%28x-a%29%28b-x%29%7D%5C%2C%5Cmathrm%20dx)
Complete the square to get
![(x-a)(b-x)=-(x-a)(x-b)=-x^2+(a+b)x-ab=\dfrac{(a+b)^2}4-ab-\left(x-\dfrac{a+b}2\right)^2](https://tex.z-dn.net/?f=%28x-a%29%28b-x%29%3D-%28x-a%29%28x-b%29%3D-x%5E2%2B%28a%2Bb%29x-ab%3D%5Cdfrac%7B%28a%2Bb%29%5E2%7D4-ab-%5Cleft%28x-%5Cdfrac%7Ba%2Bb%7D2%5Cright%29%5E2)
and let
for brevity. Note that
![c=\dfrac{(a+b)^2}4-ab=\dfrac{a^2-2ab+b^2}4=\dfrac{(a-b)^2}4](https://tex.z-dn.net/?f=c%3D%5Cdfrac%7B%28a%2Bb%29%5E2%7D4-ab%3D%5Cdfrac%7Ba%5E2-2ab%2Bb%5E2%7D4%3D%5Cdfrac%7B%28a-b%29%5E2%7D4)
![I=\displaystyle\int_p^q\sqrt{c-\left(x-\dfrac{a+b}2\right)^2}\,\mathrm dx](https://tex.z-dn.net/?f=I%3D%5Cdisplaystyle%5Cint_p%5Eq%5Csqrt%7Bc-%5Cleft%28x-%5Cdfrac%7Ba%2Bb%7D2%5Cright%29%5E2%7D%5C%2C%5Cmathrm%20dx)
Make the following substitution,
![x=\dfrac{a+b}2-\sqrt c\,\cos\theta](https://tex.z-dn.net/?f=x%3D%5Cdfrac%7Ba%2Bb%7D2-%5Csqrt%20c%5C%2C%5Ccos%5Ctheta)
![\mathrm dx=\sqrt c\,\sin\theta\,\mathrm d\theta](https://tex.z-dn.net/?f=%5Cmathrm%20dx%3D%5Csqrt%20c%5C%2C%5Csin%5Ctheta%5C%2C%5Cmathrm%20d%5Ctheta)
and the integral reduces like before to
![I=\displaystyle\int_P^Q\sqrt{c-c\cos^2\theta}\,\sin\theta\,\mathrm d\theta](https://tex.z-dn.net/?f=I%3D%5Cdisplaystyle%5Cint_P%5EQ%5Csqrt%7Bc-c%5Ccos%5E2%5Ctheta%7D%5C%2C%5Csin%5Ctheta%5C%2C%5Cmathrm%20d%5Ctheta)
where
![p=\dfrac{a+b}2-\sqrt c\,\cos P\implies P=\cos^{-1}\dfrac{\frac{a+b}2-p}{\sqrt c}](https://tex.z-dn.net/?f=p%3D%5Cdfrac%7Ba%2Bb%7D2-%5Csqrt%20c%5C%2C%5Ccos%20P%5Cimplies%20P%3D%5Ccos%5E%7B-1%7D%5Cdfrac%7B%5Cfrac%7Ba%2Bb%7D2-p%7D%7B%5Csqrt%20c%7D)
![q=\dfrac{a+b}2-\sqrt c\,\cos Q\implies Q=\cos^{-1}\dfrac{\frac{a+b}2-q}{\sqrt c}](https://tex.z-dn.net/?f=q%3D%5Cdfrac%7Ba%2Bb%7D2-%5Csqrt%20c%5C%2C%5Ccos%20Q%5Cimplies%20Q%3D%5Ccos%5E%7B-1%7D%5Cdfrac%7B%5Cfrac%7Ba%2Bb%7D2-q%7D%7B%5Csqrt%20c%7D)
![I=\displaystyle\frac{\sqrt c}2\int_P^Q(1-\cos(2\theta))\,\mathrm d\theta](https://tex.z-dn.net/?f=I%3D%5Cdisplaystyle%5Cfrac%7B%5Csqrt%20c%7D2%5Cint_P%5EQ%281-%5Ccos%282%5Ctheta%29%29%5C%2C%5Cmathrm%20d%5Ctheta)
(Depending on the interval [<em>p</em>, <em>q</em>] and thus [<em>P</em>, <em>Q</em>], the square root of cosine squared may not always reduce to sine.)
Resolving the integral and replacing <em>c</em>, with
![c=\dfrac{(a-b)^2}4\implies\sqrt c=\dfrac{|a-b|}2=\dfrac{b-a}2](https://tex.z-dn.net/?f=c%3D%5Cdfrac%7B%28a-b%29%5E2%7D4%5Cimplies%5Csqrt%20c%3D%5Cdfrac%7B%7Ca-b%7C%7D2%3D%5Cdfrac%7Bb-a%7D2)
because
, gives
![I=\dfrac{b-a}2(\cos(2P)-\cos(2Q)-(P-Q))](https://tex.z-dn.net/?f=I%3D%5Cdfrac%7Bb-a%7D2%28%5Ccos%282P%29-%5Ccos%282Q%29-%28P-Q%29%29)
Without knowing <em>p</em> and <em>q</em> explicitly, there's not much more to say.